KESESUAIAN LEMBAR KERJA PESERTA DIDIK ELEKTRONIK BERBASIS MODEL PROBLEM BASED LEARNING KONSEP SISTEM EKSKRESI PADA MANUSI - Munada, Syahrial; Noorhidayati, Noorhidayati; Halang, Bunda (BIOEDUKASI (Jurnal Pendidikan Biologi), 2024)
Education in the 21st century is becoming increasingly useful for nurturing students to have skills, innovation, and skills in using technology. The choice of Electronic Student Worksheets as learning media is to adapt to 21st-century developments in education because teachers are still constrained by innovation in learning media to support the learning process so that it is more varied and not easily bored, and students can be skilled in using technology. This research aims to describe the suitability of the results of developing Electronic Student Worksheets. This research and development uses the 4D model Thiagarajan, dkk. (1974) which was applied to the Disseminate stage and carried out limited to the research site and published in scientific journal articles adjusted to take into account aspects of time and cost so that it was simplified. The technique for collecting research data is using a suitability instrument consisting of 29 aspect items with a score range of 1 to 5. The subjects are supervisors 1 and 2 of biology education at FKIP Universitas Lambung Mangkurat and 1 educator at SMAN 4 Banjarmasin. Based on the research results, the average suitability score was 4.37 in the very suitable category. This shows that electronic Student Worksheets based on the PBL model are suitable for use in learning, daily life, and the demands of the human excretory system concept curriculum so that it can be used as a learning medium based on the suitability criteria that have been created.